Test of DMB-T Signal Based on Software Defined Radio Technique - Shanshan Li; Jian Zhou; Yi Zhang (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
With the release of the standard, digital television terrestrial broadcasting is being gradually extended in many places. In order to speed up the extension and the application, also to evaluate the existing digital television terrestrial   broadcasting  system, we need a easy-to-use signal  analysis  and measurement  system. The traditional signal measurement method is through the special hardware circuit to realize, but that method is high cost, and the system structure is complex and single function. To improve the flexibility of the system , we realize the system based on virtual instrument technology. In hardware section, this thesis described the block diagram of the system and the introduction of the NI vector signal analyzer. In software part, this thesis described the overall test system based on LabVIEW and the realization of the system features multi-threading, each step of synchronization signals achieved. DOI: http://dx.doi.org/10.11591/telkomnika.v11i3.2308